Enabling the Facile Synthesis of Arenes by Transition Metal Catalyzed Decarbonylation Methodology. Issue 12 (28th October 2021) - Sinha, Soumya Kumar; Roy, Triptesh Kumar; Modak, Atanu; Maiti, Debabrata
Abstract: Transition metal‐catalyzed decarbonylation is an essential paradigm of synthetic organic chemistry. Decarbonylation offers a unique pathway to decoding the skeletal structure of arenes and enabling easy synthesis of structurally complicated molecules. Due to the omnipresence of carbonyl groups in a wide array of synthetically important complex molecules, the variety and scope of these transformations are enormous. As a result, the development of transition metal catalysts in such a simple decarbonylation reaction ranks among one of the most important topics in synthetic organic chemistry. Transition metals that have been employed range from 3d metals like V to second‐row transition metals like Pd. The growing potential of this methodology has driven the pioneers of synthetic organic chemistry into delving into the details of this transition metal‐catalyzed decarbonylation pathways. This review aims to take the readers through the employment of transition metals in various decarbonylation processes developed by our group, sticking not only to the scope and diversification of synthetically complex molecules, but also enabling the readers to understand the mechanistic insights, through computational and kinetic studies put forward in such reaction protocol, hoping to pave the way for future organic chemists to delve and hopefully solve the unique problems associated with this protocol. Abstract : The growing potential of decarbonylation methodology has driven the pioneers of synthetic organic chemistry into delving into the details of this transition metal‐catalyzed decarbonylation pathways. This review aims to take the readers through the employment of transition metals in various decarbonylation processes developed by our group, sticking not only to the scope and diversification of synthetically complex molecules, but also enabling the readers to understand the mechanistic insights, through computational and kinetic studies put forward in such reaction protocol.